Spontaneous elimination of gossypiboma: A case report (International Seven Journal of Multidisciplinary, 2024)
Introduction: The term gossypiboma refers to surgical items of textile matrix inadvertently left inside cavities after closure of the surgical wound. The unrecognized presence of a foreign body of any kind in the abdominal cavity after an operation is a situation rarely reported in the medical literature and surrounded by a potential for serious complications, which can evolve into a fatality. This article is an observational and descriptive case report. The information was collected by reviewing the medical records and photographic records of the surgical procedures the patient underwent. It aims to present a case of spontaneous elimination of gossypoma in a patient who had undergone a previous caesarean section. Report: Patient R.T.T.S, 17 years old, female, previously healthy, with sporadic diffuse abdominal pain for 10 months after caesarean section, with progressive worsening. One week ago, she had a significant worsening of the pain associated with constipation, difficulty in evacuating and, one day ago, anal elimination of contents similar to vegetable loofah (SIC). Physical examination revealed a slight bulge in the hypogastric region and rectal elimination of a foreign body. Discussion: Imaging methods are important allies in identifying this type of problem. The surgical approach adopted will depend on the clinical and radiological presentation of the gossypiboma. In the case reported here, we opted for rectal removal of the foreign body while preserving the integrity of the abdominal cavity, as the patient had no symptoms of abscess or fistulae. She evolved in the post-operative period in good clinical condition. Cases like this are increasingly reinforcing the need to adopt and strictly comply with checklists prior to surgery and at the end of surgery. In order to provide safe surgeries with excellence for patients in any institution in the country.